Revitalization of Assisted Nagari Through Research Based Community Engagement - Rizal, Yose; Efendi, Roni; Utamy, Hebby Rahmatul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
In order to advance knowledge, higher education has a duty to educate all facets of society, including the local population. Additionally, as advancing general welfare is a duty of higher education, these efforts can be carried out through fulfilling duties related to the tri-dharma of higher education, all of which are interconnected and cannot be separated from one another. One of these dharmas is community service, which is why LP2M UIN Mahmud Yunus followed this approach when performing research-based service. Prior study must be done to ensure that the service is modeled, structured, and evaluated in accordance with the needs of┬áthe aided community.